The feminist “quarantine” on hijab: a study of its two mutually exclusive sets of meanings - Hasan, Md. Mahmudul (Taylor & Francis, 2018)
The discourse on feminism is sharply polarized between those who regard hijab as essentially debilitating and those who see it as an enabling tool for dignity, selfworth and freedom. This article will discuss both the negative and positive associations of hijab and point out ways it is used by Muslim women for liberatory ends. It will go against the grain of a common argument that hijab equates seclusion and constraints on women’s participation in public life hence it is inherently oppressive. I will argue that hijab can potentially be used for diametrically opposite purposes. While acknowledging the fact that the Islamic dress code for women can be misused by patriarchal power systems as well as by women themselves, I will put forth arguments against dismissive and uncritical criticism of hijab.